Improvement in the epigenetic modification and development competence in PCOS mice oocytes by hydro-alcoholic extract of Nigella sativa during in-vitro maturation: An experimental study - Fatemeh Eini; Khojasteh Joharchi; Maryam Azizi Kutenaei; Pegah Mousavi (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Nigella Sativa (NS) and its active component, thymoquinone, have beneficial protective effects on experimental animal models of polycystic ovary syndrome (PCOS) and different human diseases. Objective: The present study aimed to investigate the effects of NS hydro-alcoholic extract (NSE) on the oocyte quality of PCOS mice during in vitro maturation. Materials and Methods: For induction of PCOS, 40 prepubertal 21-days old female B6D2F1 mice (18-22 g body weight) received subcutaneous dehydroepiandrosterone daily. After validation of the model, germinal vesicle-stage oocytes of superovulated mice were collected and placed in the culture medium containing different concentrations (0, 1, 50, and 100 μg/ml) of NSE. For the measurement of developmental competency, some mature oocytes were fertilized with epididymal spermatozoa. Other mature oocytes were assessed for oxidative stress. Also, some mRNA expression levels involved in oocyte maturation and epigenetic modification were evaluated. Results: The 50 μg/ml NSE treated group showed significantly higher r ates o f maturation, f ertilization, and blastocyst formation in comparison with both control and PCOS groups. A high level of glutathione concentration and glutathione peroxidase mRNA expression, besides a low level of reactive oxygen species content all, were observed in oocytes treated with 50 μg/ml NSE, indicating the modification of oxidative statue. Furthermore, the oocytes in the 50 μg/ml-treated group showed an upregulation of mRNA expression in epigenetic-related genes (Dnmt1 and Hdac1) and maternally derived genes (Mapk and Cdk1), correspondingly downregulation of cyclooxygenase2 mRNA expression, in comparison to other groups. Conclusion: The results of this study indicated that 50 μg/ml NSE improves oocyte maturation, oxidative statues and epigenetic modifications. These may be the all reasons for the developmental competency in the control and PCOS mice oocytes. Key words: Epigenetic modification, In-vitro maturation, Nigella sativa, Oxidative stress, Polycystic ovary syndrome.Key words: Epigenetic modification, In-vitro maturation, Nigella sativa, Oxidative stress, Polycystic ovary syndrome.}